Analisa Kegagalan Struktur Lereng Tanah Pada Jalur Ganda Dengan Menggunakan Analisis Komputasi (Studi Kasus : Sta 208 + 00 Doeble Track Kereta Api Martapura- Baturaja) - Septian, Rio Dwi; Iswan, Iswan; Zakaria, Ahmad (Universitas Lampung, 2019)
The safety level of a slope is influenced by several factors, including factors tilt and loads working on it. Slope conditions with large loads and steep slopes can cause landslides. The influence of heavy rain flushed the majority of the region martapura - baturaja cause landslides and slope at some point in double track train along 50m which have geographic condition consists of the land pile of high steep, so prone to landslides. This is certainly very dangerous for trains, and around the slopes a solution is needed that can be an alternative to make the slope safe from landslide hazards. Based on the laboratory tests that have been carried out of the samples were taken from the site, so the analysis of the existing slopes stability with computer analysis shows the condition of unstable because from the result of numerical safety value analysis 1,731 for condition 1 and 1,732 for condition 2, so that needed reinforcement on the slopes itself. From the analysis of the slopes stability which has been strengthened with a combination of retaining Wall of land and drill pile using the Computer Analysis obtained greater numerical safety value compared by only reinforced with retaining Wall land for 3,978 to condition 1 and 3,983 to condition 2, so the design of strengthening is safe and able to withstand landslide. Keyword : Borehole Data, Geoelectric, Computer Analysis using methods Fellenius